OPTIMALISASI TES DIAGNOSTIK BERBASIS IT DALAM MENINGKATKAN MUTU PEMBELAJARAN BAHASA BALI PADA KURIKULUM MERDEKA - I Kadek Mustika (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
Assessment is a very important part of learning. Assessment can be done in the form of pre-learning (diagnostics) and learning outcomes to monitor the process, progress and development of learning outcomes, as well as feedback for teachers to improve learning planning. Balinese language learning, especially in the Kurikulum Merdeka, uses diagnostic tests, formative tests, and summative tests. Diagnostic tests or pre-learning tests are related to mapping the learning styles, interests, and prior knowledge of students so that teachers can carry out differentiated learning according to the needs of students. Optimizing diagnostic tests using IT is very important to do in order to improve the quality of Balinese language learning so that it fits the needs of students and the time spent in learning also effectively.